Purchase Interest In Beauty Industry: Role Of Brand Image, Product, And Promotion - Pujiyanto, Bagas; Hendrawan, Dimas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of brand image, product quality, and online promotion on purchase interest in MS Glow facial care products among young consumers in Malang City. Design/methodology/approach – This study employs a quantitative descriptive research design. Data were collected through questionnaires distributed to 170 young consumers in Malang City using a non-probability sampling technique. The data were analyzed using multiple linear regression with IBM SPSS to test the proposed relationships among variables. Findings – The results indicate that brand image and online promotion have a positive and significant effect on purchase interest, while product quality does not have a significant effect. These findings suggest that, in highly competitive beauty markets, consumers’ purchase interest is more strongly driven by brand perception and digital promotional activities than by product quality alone. Originality/value – This study contributes to consumer behavior and digital marketing literature by highlighting the dominant role of brand image and online promotion in shaping purchase interest in the skincare industry. The findings provide practical implications for beauty brands in strengthening digital marketing strategies and brand positioning to sustain consumer engagement and competitiveness.